Perceived supervisor supports: contribution to aspiration, mastery and salience as three dimensions of achievement motivation - Karami, Roya; Ismail, Maimunah (IDOSI Publications, 2013)
This study examines the influence of perceived work and non-work supervisor supports on aspiration, mastery and salience. Aspiration, mastery and salience are the three dimensions of achievement motivation. A total of 303 Iranian extension agents were surveyed using a set of structured questionnaire. The results show that there are sequential relationships among the three dimensions of achievement motivation. The results also show that perceived supervisor work supports influence employees’ aspiration and mastery, while, supervisor non-work supports is associated with aspiration and salience. Practical and theoretical contributions of this study to human resource issues are also discussed.